KONTRUKSI KOMUNIKASI PROFETIK DALAM MEMBANGUN KEBUTUHAN PELANGGAN LEMBAGA PENDIDIKAN ISLAM - Haq, Muhammad Izzul; Mutohar, Prim Masrokan (Jurnal Isema : Islamic Educational Management, 2023)
Prophetic communication is a new term in the communication science family. Prophetic itself is everything that relies on the attitude, behavior, and words of the Prophet Muhammad. In prophetic communication there are elements of values and ethics. The focus of this research is on the construction of prophetic communication in building customer needs for Islamic education at the State Islamic Senior High School (MAN) 1 Tulungagung. Data collection through in-depth interviews, participatory observation and documentation. The results of the study mention that building customer needs through prophetic communication is manifested by SEHAT (Who am I, Empathy, Reliable, Enthusiastic, Responsive). This concept is accompanied by examples of prophetic communication practices that occur in the madrasah environment. This research is practically used in Islamic education management science, especially in actualizing changes in conditions and situations. Furthermore, this research aims to be developed further